The role of particle physico-chemical properties in pulmonary drug delivery for tuberculosis therapy. (December 2014) - Mortensen, Ninell P.; Durham, Phillip; Hickey, Anthony J.
Abstract There is increasing interest in the use of inhaled aerosol drug therapy for the treatment of tuberculosis (TB). A number of methods of preparation of particles have been employed including spray drying, solvent evaporation, emulsion and phospholipid methods to create microparticles, macroaggregated nanoparticles, solid lipid nanoparticles and liposomes. Each of these methods involves the use of different proportions of additives to aid in the particle formation or to achieve important physico-chemical properties such as ease of dispersion. While these approaches all have merit their practical value is limited by constraints on dose and means of delivery as an aerosol in order to achieve a therapeutic effect. A review of a number of approaches is presented and placed in the context of the need for effective aerosol delivery systems for the treatment of TB as a guide to selection of appropriate excipients, processes and delivery strategies to support product development activities.